Interannual fires as a source for subarctic summer decadal climate variability mediated by permafrost thawing - Ji-Eun Kim; Ryohei Yamaguchi; Keith B. Rodgers; Axel Timmermann; Sun-Seon Lee; Karl Stein; Gokhan Danabasoglu; Jean-Francois Lamarque; John T. Fasullo; Clara Deser; Nan Rosenbloom; Jim Edwards; et al. (npj Climate and Atmospheric Science, 2023)
Abstract Climate model simulations run under the Coupled Model Intercomparison Project Phase 6 (CMIP6) use an inhomogeneous biomass burning aerosol (BBA) emission dataset, which exhibits pronounced interannual variability from 1997–2014 due to the infusion of satellite data. Using the Community Earth System Model version 2 Large Ensemble (CESM2-LE) with original and smoothed CMIP6 BBA forcings, we show that the CMIP6 data inhomogeneity causes spurious decadal subarctic land warming. During years with reduced aerosol concentrations, increased solar radiation can trigger abrupt subarctic permafrost thawing, increased soil water drainage, upper soil drying, and subsequent surface warming. This slow process, which is further amplified by nonlinear cloud-aerosol interactions, cannot be completely offset during years of increased aerosol fluxes, thereby reddening surface temperature spectra in response to large-amplitude interannual aerosol forcing. More generally, our CESM2 experiments identify a pathway for generating decadal variability in high latitudes, involving interannual shortwave forcing and slow nonlinear soil responses.